Financial Tech and Verbal Sexual Harassment on TikTok: A Phenomenological Study on Mental Health Education for Female Digital Workers - Verica Sofie Putibungsu; Rr Setyawati (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2026)
The rapid growth of financial technology and social commerce has expanded employment opportunities for female TikTok live streaming hosts while simultaneously increasing their exposure to verbal sexual harassment, posing significant challenges to mental health and educational psychology. This study explored the emotional labor of female TikTok hosts in coping with verbal sexual harassment during live broadcasts. Using an interpretive phenomenological approach, data were collected through semi-structured interviews and digital documentation from four female TikTok hosts and analyzed using Braun and Clarke’s thematic analysis. Five themes emerged: professionalism as a job demand, recurring verbal sexual harassment, displaying false amiability despite discomfort, emotional exhaustion caused by continuous emotion regulation, and adaptive coping strategies. The findings reveal that participants engaged in intensive emotional labor by suppressing negative emotions to maintain professionalism and secure their livelihoods, resulting in emotional dissonance. These findings provide empirical evidence for educational psychology and contribute to the development of mental health education frameworks that promote digital safety and psychological well-being among female workers in technology-driven workplaces